Flexible ultracapacitor device fabricated with an organic electrode material- naphthalene diimide nitrile/reduced graphene oxide - Deshmukh, Ashvini B.; Biradar, Madan R.; Pawar, Meenakshi D.; Bhosale, Sidhanath V.; Shelke, Manjusha V. (Journal of Energy Storage, 2022)
In this work, we have demonstrated a high-performance flexible supercapacitor electrode based on reduced graphene oxide (rGO) and naphthalene diimide nitrile (NDI-CN) composite. The rGO/NDI-CN composite was prepared by a simple approach. This composite was well characterized using various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) etc. Besides, the pi -pi stacking of NDI-CN on rGO surface was confirmed using UV-vis and FTIR techniques. As fabricated rGO/NDI-CN composite was examined as an electrode material for the supercapacitor applications. The rGO/NDI-CN electrode has delivered an excellent specific capacitance (C-sp) of 336 F g(-1) at 0.5 A g(-1)current density. The fabricated supercapacitor (SC) displays robustness with 80 % capacitance retention over 10,000 cycles at higher current density of 10 A g(-1). To further explore the real-world application of electrode materials, the corresponding flexible supercapacitor was designed and examined. The flexible device exhibited an energy density of 9.54 mu Wh cm(-2) at a power density of 0.3 mWcm(-2). These results confirmed that the rGO/NDI-CN electrode material has good potential as an energy storage device. Furthermore, the facile construction and fabrication of flexible device displayed operation of LED when fully charged. The assembled flexible supercapacitor device could be bent and twisted, signifying the potential to be used in practical applications in various high-performance electrochemical devices.
Keywords: flexible supercapacitor; Naphthalene diimide; Organic molecule electrodes; pi -pi interaction; rGO